Service Quality Perception and Service Satisfaction of COVID-19 Vaccination in Indonesia: A Participants Vaccination Perspective - Intan Zainafree; Chatila Maharani; Fitri Indrawati; Bambang Wahyono; Nadia Syukria; Maria M. Rosaria Patriajat; Mohammad Abdul Hakam; Rahma Defi; Hanif Pandu Suhito (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
The COVID-19 vaccine is a crucial effort to break the chain of transmission of COVID-19. To achieve optimal, effective, and efficient results in community program implementation, monitoring and evaluation are essential. The purpose of this study was to evaluate the implementation of COVID-19 vaccination in Semarang. So, it was known that service quality perception, service satisfaction, and willingness to recommend vaccination to others. This study is an analytic observational study with a cross-sectional design in 2022. The total number of respondents was 512 people. Data collection was carried out directly by visiting respondents who had received COVID-19 vaccinations at public health centers and vaccination centers. The data obtained is then processed and analyzed with the final model using Binary Logistic Regression. Respondents with basic education (4.67 ± 0.449) and those using the collective registration mechanism (4.51 ± 0.495) showed a positive correlation with perceived service quality. Of the 9 procedural suitability items, 4 received higher satisfaction scores: staff asking about regular medication use (4.41 ± 0.612), confirmed COVID-19 history (4.42 ± 0.598), close contact history (4.42 ± 0.609), and post-vaccination observation for side effects (4.43 ± 0.608), all with p-value < 0.05. Overall, respondents were satisfied with the service quality, with 26.5% willing to recommend vaccination to others. This indicates that the COVID-19 vaccination service is running effectively and appropriately.